PENGALAMAN NELAYAN BINTARO GAPURA SUMENEP DALAM PENENTUAN ARAH KIBLAT DAN WAKTU SHALAT (PERSPEKTIF FIQH HISAB-RUKYAT) - Achmad Mulyadi (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2018)
Facing the Qibla becomes one of the absolute requirements in doing prayer, except in some concequencies, first, the humans are in fear, in a forced condition and in a serious ill; second, they are praying during travelling on the vehicles. The fishermen of Bintaro Gapura Sumenep belong to a society which are often faced to the exception to face Qibla in doing their prayer. The condition while fishing and the boat used become the factors in the easinesss in doing the prayer. In the Fiqh Hisab- Rukyah perspective analysis, it is explained how to decide the position of Qibla in doing prayer in the middle of the sea. The data is collected through the steps of qualitative research. It starts from non-participant observation, unstructured interview and documentation. There are many challeges faced by the fishermen in doing the prayer, from the sea breeze and wave condition to the work in the sea which takes so much time. In the limited condition, they are rarely think about the completeness and the valid requirement of the prayer, especially the matter of facing Qibla. The majority of them think that the qibla is on the west of the direction. To adjust the compass’ accuracy of the west, they just mark off the direction of the sun’s shift and set. They do not know whether the sun ‘s position is on the south or north of the equator. The standart is based on the verification of the compass’ or remote’s west. They do the prayer based on the right time to pray by looking at the time or another natural markers.